Tunable Structure and Properties of Co-Evaporated Co–C60 Nanocomposite Films - Ziyang Gu; Yiting Gao; Zhou Li; Weihang Zou; Keming Li; Huan Xu; Zhu Xiao; Mei Fang (Nanomaterials)
Magnetic nanoparticles (NPs) hold great promise for both fundamental research and future applications due to their unique structural features, high specific surface area, and tailored physical properties. Here, we present a convenient thermal co-evaporation approach to deposit Co–C60 composite films with controlled composition, structure, morphology, and tunable performances, specifically designed for spintronic device applications. By tuning the growth rates of Co and C60 during co-evaporation, the composition of the films can be tuned with different ratios. With a Co/C60 ratio of 5:1, ~300 nm clusters are formed in the films with increased coercivity compared with pure Co films, which is attributed to the interfaces in the composite film. The magnetoresistance (MR), however, becomes dominated by organic semiconductor C60 with ordinary magnetoresistance (OMAR). By increasing the composition of C60 to the ratio of 5:2, the particle diameter decreases while the height increases dramatically, forming magnetic electrodes and, thus, nano-organic spin valves (OSV) in the composite films with giant magnetoresistance (GMR). The work demonstrates a versatile approach to tailoring the structural and functional properties of magnetic NP-composite films for advanced spintronic applications.